Method-specific suicide mortality and its spatial autocorrelation among residents in Hubei province, 2019: a vital registry-based analysis - Jing-ju PAN; Meng-ge ZHOU; Lan ZHANG (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To analyze method-specific suicide mortality and its spatial distribution among residents in Hubei province in 2019 for providing evidences to the development of effective measures on suicide prevention. Methods The data on suicide deaths among permanent residents over 10 years old in Hubei province during 2019 were extracted from the Death Reporting System of Chinese Center for Disease Control and Prevention. SAS software and ArcGis 10.6 were utilized in analyses on suicide methods and its spatial autocorrelation. Results During the year in the residents, the number of suicide deaths, mortality and standardized mortality rate (SMR) were 7 868, 14.88/100000 and 12.56/100 000, respectively. The top three methods for all the registered suicide mortalities were pesticide poisoning (with the death number of 3 481, the mortality rate of 6.58/100 000, and the SMR of 5.36/100 000), hanging (2 497, 4.72/100 000, and 3.87/100 000), jumping from a high place (709, 1.34/100 000, 1.33/100 000) and the deaths attributed to the three methods accounting for 84.99% of all suicide deaths. The top three methods for the male, female and urban suicide mortalities among residents were the same as for all the suicide mortalities; while for the rural suicide mortalities, the top two methods were the same but the third method was other substances poisoning. Jumping from a high place was the major suicide method for the suicide mortalities aged 10 - 24 and 25 - 44 years; whereas, for the suicide mortalities aged 45 - 64 years and 65 years and above, the major suicide method was pesticide poisoning. Global spatial autocorrelation analysis showed that there were spatial clustering in suicide mortality, the main suicide methods of pesticide poisoning, hanging, and jumping from a high place, with the global Moran's indicies of 0.473, 0.387, 0.482, and 0.244 (P < 0.001). Local spatial autocorrelation analysis revealed high-high clustering of suicide mortality in some districts/prefectures of 7 municipalities, low-low clustering in some urban districts of 2 municipalities, high-low clustering in one prefectures, and low-high clustering in one prefecture and two districts of a prefecture; local spatial autocorrelation analysis also revealed various types of clustering of suicide methods as following: high-high clustering of pesticide poisoning in 5 counties and 5 prefectures, high-high clustering of hanging in some districts/counties/prefectures in western region of Hubei province, low-low clustering of pesticide poisoning and hanging in some urban districts of two municipalities, and high-high clustering of jumping from a high place in some urban districts of two municipalities. ConclusionAmong suicide mortalities during 2019 in Hubei province, pesticide poisoning, hanging, and jumping from a high place were main methods and there were obvious spatial clustering and significant gender, age, and regional differences in the main suicide methods.